Proposal for “Fayton” carpooling platform in Azerbaijan - Hasanov, Fikrat (ADA University, 2020)
This business plan introduces a business idea in regard to the establishment of a company providing carpooling services. It aims at justifying the business idea as a viable project worth investing in, providing a market research, organizational, marketing strategies and financial forecasting. Carpooling refers to the practice of the sharing of journeys by drivers and riders who go in the same direction even if the starting point and destination of their trips are not the same. Ridesharing practices become increasingly popular around the world. Especially popular are on-demand ridesharing services such as Uber, Lyft etc., which have emerged as a strong substitute for traditional taxi, allowing drivers to make a profit out of the service they provide to riders. Carpooling though also based on the sharing of journeys differs significantly from the on-demand ridesharing services. Carpooling does not allow drivers to make a profit out of the trip they share with riders. The fare paid by riders is enough only to compensate for the cost of the trips for the driver, which includes fuel, toll, parking etc. Thus, by carpooling, drivers get a chance to reduce or fully cover the cost of a trip, while riders get to pay less for a ride than they would have to pay for a trip on the public transportation or other services. By travelling in private vehicles, riders gain an opportunity to travel not only affordably but also more comfortably and faster than they would in the public transportation. By increasing the car occupancy rates, carpooling contributes to the reduction of congestion and is promoted as an environmentally friendly practice and promoted by the public authorities in many countries. Carpooling can be arranged informally but also online platforms can help match drivers and riders going in the same direction, which have been the driver behind the recent surge in popularity of carpooling. In Azerbaijan, on-demand ride-sharing services have gained popularity over the last several years with both international and local companies filling in the industry in abundant numbers. As of carpooling, however, it has been only informally practiced. There is a lack of a company that provides a platform providing a service of matching of drivers and riders for carpooling trips. “Fayton” aims at being the first entrant to this industry in Azerbaijan by offering a matching service for carpooling. There are various factors that can make a carpooling platform a valuable business opportunity in Azerbaijan. Currently, for long-distance trips, those who do not have a car have to use the public transportation services such as buses, trains. However, their comfortability and service frequency and other factors do not satisfy many riders. Within the BMA, those who do not own a personal car have to rely on the poor-quality public transportation. App-based carpooling would enable to save costs and riders to travel affordably and more comfortably. “Fayton” will provide matching services for two types of carpooling: 1) Matching of drivers and riders for long distance trips of at least 100 km throughout Azerbaijan 2) Matching of drivers and riders for commuting (mainly but not limited to) trips within the Baku Metropolitan Area (BMA), which covers the Greater Baku (all 12 districts of Baku), Sumgait and the district of Absheron. For “Fayton”, the minimum length of a long-distance trip will be 100 kms. Drivers will have a chance to post announcements on their upcoming trip providing information about routes and the fare. When drivers generate an announcement, the software of “Fayton” will calculate the cost of the trip and will allow the driver to set the charge by deviating at most 50% from the cost provided by the software. Riders will pay by cash as cashless transactions are not still very popular in Azerbaijan. The second type of carpooling will be geographically limited only to the trips over 15 km within the Baku Metropolitan. It targets mainly the BMA residents commuting to downtown Baku from the settlements remote from it in various parts of the BMA for work, study and other activities regularly. A fixed commission of 0.2 AZN per trip will be charged regardless of the length of the trip. “Fayton” will not impose a cap on how many trips drivers can post announcements of daily for both long-distance and commute carpooling. This study used a variety of research methods for the market research, assessment of opportunities and challenges the company might face. A web-based questionnaire among the BMA residents was used to find out about the travel patterns of respondents, their awareness of carpooling and attitudes towards it. To analyze the competitiveness of the environment in which the business will operate, Porter’s 5 forces framework was applied. PEST analysis was done to assess the factors characterizing the political, economic, social and technical settings within which the business will operate. SWOT analysis was also conducted to assess strengths, weakness, opportunities and threats in relation to the strategic planning of the project. The marketing plan provides information on which marketing strategies will be employed by the company. The marketing of the company will be based on social media advertising predominantly. The financial plan provides assumptions on which the financial forecasting is carried out and income statement, cash flow, sensitivity analysis and exit options.
Keywords: Business; Car pools -- Azerbaijan.; Paratransit services -- Azerbaijan.; Transportation infrastructure -- Azerbaijan.